Penyuluhan google classroom dan google meet kepada guru sdn wonoayu dalam kegiatan kkn back to village - Ihyana Lutfianda; Muhammad Bahrul Ulum (Jurnal Abdi Masyarakat, 2021)
The COVID-19 pandemic that has spread across all countries requires humans to avoid crowds, affecting students' learning activities in primary schools. SDN Wonoayu is located in the Pilangkenceng sub-district, Madiun district, carrying out online learning activities for the semester 2019/2020 using the Whatsapp group. The teachers of SDN Wonoayu had difficulty in recapitulating their assignments. Also, some parents faced the same, particularly their challenges in utilizing Whatsapp for their child's learning media and their business media. Students were less able to understand because of independent learning. It required direct interaction to study the material or practice memorization. This program was expected to assist in uploading material, implementing assignment collection, and assisting teacher assessments of students during learning at home using Google Classroom. The Google Form's features were used as a medium for quizzes so that the grades automatically could be easily recapitulated by teachers. Using Google Meet could help learning media for both students and teachers to interact virtually to review material or memorization practices. The work program was carried out with the following steps: introduction (observation and problem identification), looking for literature and information that would be used as additional learning media, counsellingLearning Media learning media to teachers according to health protocols, applying learning media to students, and mentoring teachers. In summary, this KKN program could meet success indicators of> 70% based on questionnaire data given to Islamic Education Teachers, PJOK Teachers, and Grade 4 Student Samples.